2014
DOI: 10.4025/actascibiolsci.v36i4.23168
|View full text |Cite
|
Sign up to set email alerts
|

<b>Ultrastructural aspects of the tongue in Magellanic Penguins <i>Spheniscus magellanicus</i> (Forster, 1781)

Abstract: ABSTRACT. The tongue of birds presents diversified morphologic characteristics, related directly their feeding habits and may be adapted to food capture. Penguins of the Spheniscidae family are pelagic birds that are totally adapted to the marine environment. The objective of this study was to describe the morphology of the tongue in Magellanic penguins (Spheniscus magellanicus). In order to investigate these characteristics, six tongues of juvenile S. magellanicus were collected and their morphology analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…This finding is obviously different from the keratinized lingual epithelium detected in Japanese quail (Warner et al, 1967) and in most birds as reported by Kobayashi et al (1998). the tongue of the Magellanic penguin showed a highly keratinized epithelium both in the dorsal and ventral regions (Guimarães et al, 2014) as it was observed with other penguin species (Kobayashi et al, 1998) and in other birds, the cormorant (Jackowiak et al, 2006), the oriental scops owl, and the Japanese pigmy woodpecker (Emura et al, 2009 a, b), whose feeding habits depend on a more rigid and resistant tongue structure. Our study showed that the dorsal surface of the lingual apex of ansa clypeata is thicker than the dorsal surface of the lingual apex of anas Penelope.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This finding is obviously different from the keratinized lingual epithelium detected in Japanese quail (Warner et al, 1967) and in most birds as reported by Kobayashi et al (1998). the tongue of the Magellanic penguin showed a highly keratinized epithelium both in the dorsal and ventral regions (Guimarães et al, 2014) as it was observed with other penguin species (Kobayashi et al, 1998) and in other birds, the cormorant (Jackowiak et al, 2006), the oriental scops owl, and the Japanese pigmy woodpecker (Emura et al, 2009 a, b), whose feeding habits depend on a more rigid and resistant tongue structure. Our study showed that the dorsal surface of the lingual apex of ansa clypeata is thicker than the dorsal surface of the lingual apex of anas Penelope.…”
Section: Discussioncontrasting
confidence: 73%
“…Comparative studies that have been made on the tongue of different vertebrate species suggest morphological adaptations throughout the process of evolution. These evolutionary changes are considered the principles for the progress in food intake and occupation of different habitats (Iwasaki, 2002 andGuimarães et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hummingbird tongues entirely lack papillae, a rare condition in vertebrate tongues ( Schwenk, 2000 ; Iwasaki, 2002 ) and even among birds (review in Erdoğan & Iwasaki, 2014 ). Avian lingual papillae are involved in manipulation of solid food (e.g., prey apprehension, holding, cutting, filtering, shelling, Iwasaki, Asami & Chiba, 1997 ; Kobayashi et al, 1998 ; Jackowiak et al, 2010 ; Jackowiak et al, 2011 ; Guimarães et al, 2014 ; Skieresz-Szewczyk & Jackowiak, 2014 ) and caudal intraoral transport of solid items (review in Parchami, Dehkordi & Bahadoran, 2010 ). Hummingbirds have remarkable feeding modes; first, about half of their diet (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Avian lingual papillae are involved in manipulation of solid food (e.g. prey apprehension, holding, cutting, filtering, shelling, Iwasaki et al 1997;Kobayashi et al 1998;Jackowiak et al 2010;Guimarães et al 2014;Skieresz-Szewczyk and Jackowiak 2014) Harper et al 2013) or lorikeets (Homberger 1980, p. 41). Second, the other half of their diet (cf.…”
Section: Gross Morphology Of Hummingbird Tonguesmentioning
confidence: 99%